Natural history and clinical parameters of chemotherapy-induced dilated cardiomyopathy. (3rd October 2022) - Lalario, A; Del Mestre, E; Lo Casto, M; Nuzzi, V; Manca, P; Bromage, D; Barbati, G; Merlo, M; Sinagra, G; Cannata, A
Abstract: Background: Chemotherapy-induced dilated cardiomyopathy (CI-DCM) is a well-recognized phenotype of non-ischemic dilated cardiomyopathy (DCM), characterized by poor outcomes. However, a detailed comparison between idiopathic DCM (iDCM) and CI-DCM is still lacking. Methods: All consecutive DCM patients enrolled in the Trieste Muscle Heart Disease Registry were analyzed. CI-DCM and iDCM were defined according to current recommendations. The primary study outcome measure was all-mortality death and secondary outcomes were a) a composite of cardiovascular death/heart-transplantation/ventricular-assist-device implantation, and b) major ventricular arrhythmias. Results: The study included 551 patients (499 iDCM and 52 CI-DCM). At enrolment, compared to iDCM, CI-DCM patients were older (51±14 years vs 58±3 years respectively, p<0.001) and had a higher left ventricular ejection fraction (35%±10 vs 32%±9, p=0.03). Over a median follow-up of 90 months (IQR 54–140 months), CI-DCM patients had a higher incidence of all-cause mortality compared to iDCM (36.5% vs 8.4% in CI-DCM and iDCM respectively, p<0.001), while the incidence of major ventricular arrhythmias was higher in the iDCM group compared to CI-DCM (4% vs 0%, in CI-DCM and iDCM respectively, p=0.03). The risk of the composite outcome was comparable between the two groups (p=0.91). At Cox multivariable analysis, the diagnosis of CI-DCM emerged as independently associated to primary outcome (HR 6.42, 95% CI 2.52–16.31, p<0.001). Conclusions: In a well-selected DCM cohort, patients with a chemotherapy-induced aetiology had a higher incidence of all-cause mortality compared to iDCM. Conversely, the incidence of life-threatening ventricular arrhythmic events was higher among patients with iDCM. Funding Acknowledgement: Type of funding sources: None.